Surface terminations of hematite (α-Fe2O3) exposed to oxygen, hydrogen, or water: dependence on the density functional theory methodology. (14th June 2018) - Wang, Richard B; Hellman, Anders
Abstract: Hematite ( α -Fe2 O3 ) is the most stable and abundant iron oxide in nature, and is used in many important environmental and industrial technologies, such as waste-water treatment, gas sensors, and photoelectrocatalysis. A clear understanding of the structure, composition, and chemistry of the hematite surface is crucial for improving its function in these technologies. Here we employ density functional theory (DFT) together with the DFT+ U approach using semi-local functionals, as well as hybrid functionals, to study the structure, stability, and electronic properties of the (0 0 0 1) surface exposed to oxygen, hydrogen, or water. The use of hybrid functionals allow for a description of strong correlation without the need for atom-specific empirical parameters (i.e. U ). However, we find that PBE+ U, and in part also PBE, give similar results as the hybrid functional HSE(12%) in terms of structure optimization. When it comes to stability, work function, as well as electronic structure, the results are sensitive to the choice of functionals, but we cannot judge which level of functional is most appropriate due to the lack of experimental observations.